2001
DOI: 10.1007/s100380170097
|View full text |Cite
|
Sign up to set email alerts
|

Screening for deletions in interval D16–22 of the Y chromosome in azoospermic and oligozoospermic Japanese men

Abstract: The genetic basis of infertility remains unclear in a majority of infertile men. In this study, the Y chromosome long arm involving the DAZ (deleted in azoospermia) gene was screened in order to evaluate the occurrence of microdeletion in Japanese infertile men. One hundred and fifty-seven infertile Japanese men with azoospermia and oligozoospermia were analyzed for microdeletions in interval D16-22 of the Y chromosome, using polymerase chain reaction with sequence-tagged site markers. Sixteen sets of oligonuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Thangaraj et al (2003) also observed the same frequency of AZFc (3.5%) in azoospermic patients in the Indian population. The changes in the prevalence are due to either small sample size or endocrine disorders, or an unknown environmental factor may be important in influencing the frequency, as has also been documented in different populations of male infertility (Chiang et al, 2000;Kato et al, 2001;Madgar et al, 2002;Sawai et al, 2002;Tse et al, 2002). In the Caucasian population, the frequency of Y-chromosome microdeletion is small; 1% (Pryor et al, 1997) and 3% (Osterlund et al, 2000) have been reported in the Swedish population and 20% in the New Zealand population (Kerr et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Thangaraj et al (2003) also observed the same frequency of AZFc (3.5%) in azoospermic patients in the Indian population. The changes in the prevalence are due to either small sample size or endocrine disorders, or an unknown environmental factor may be important in influencing the frequency, as has also been documented in different populations of male infertility (Chiang et al, 2000;Kato et al, 2001;Madgar et al, 2002;Sawai et al, 2002;Tse et al, 2002). In the Caucasian population, the frequency of Y-chromosome microdeletion is small; 1% (Pryor et al, 1997) and 3% (Osterlund et al, 2000) have been reported in the Swedish population and 20% in the New Zealand population (Kerr et al, 2000).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, about 10% to 15% of idiopathic cases of azoospermia and severe oligozoospermia have microdeletions in AZF regions as the etiologic factor [12][13][14]. The frequency of Y chromosome microdeletions varies between 1% [15] and 55% [16] in the worldwide whereas the few studies performed in Asian male populations showed frequencies of 7.6% to 16.5% in Japan [17][18][19][20][21][22], 11.0% to 19.4% in China [23,24], 10.6% to 11.7% in Taiwan [25,26], 6.4% in Hong Kong [27] and 2.0% to 12.0% in India [12,28,29]. A recently published study reported that the cumulative frequency of Y chromosome microdeletions was 3.5 % in infertile males [30].…”
Section: Abstract Y Chromosome Microdeletion Chromosomal Abnormalitmentioning
confidence: 99%
“…In particular, close relationships between microdeletions in the Y chromosome and spermatogenic failure have been reported (Pryor et al 1997;Kostiner et al 1998;Vogt 1998;McElreavey and Krausz 1999;Foresta et al 2001;Kato et al 2001;Kleiman et al 2001;Simoni 2001). About 10% of infertile males with azoospermia and oligozoospermia have Y chromosomal microdeletions around the AZF region.…”
Section: Discussionmentioning
confidence: 94%
“…PCR was performed using 16 sets of primers located in the interval D16-22 of the Y chromosome (sY138, sY233, sY240, sY245, sY277, sY254, sY283, sY255, sY236, sY267, Fig. 1a-c sY272, sY269, sY273, sY158, sY159, and sY160 (Vollrath et al 1992), as described previously (Kato et al 2001). E76 primer (ACACAGAGCAAGGCCA GAAT) and E77 primer (CTTCATGGGCCTGAACT GAT) (Ma et al 1993) were used as positive controls.…”
Section: Introductionmentioning
confidence: 99%